EPIPHYTIC AND ENDOPHYTIC PHYLLOSPHERE MICROFLORA OF CASSYTHA FILIFORMIS L. AND ITS HOSTS - Mukhtar, Irum; Mushtaq, Sobia; Ali, Amna; Khokhar, Ibatsam (Ecoprint: An International Journal of Ecology, 2011)
In the present study, samples of Cassytha filiformis L. and healthy leaves of two of its host plants viz. Bougainvillea spectabilis Willd (Nyctaginaceae) and Citrus aurantifolia Swingle (Rutaceae) were collected simultaneously from different areas of Lahore, Pakistan. To analyze epiphytic microflora, washings of host leaf/parasite stem were used for the isolation. For endophytic microbes, sterilized homogenized host leaf/parasite stem tissue mixture was plated separately on 2% MEA and LB media for bacterial and fungal isolation. Each fungal colony was purified and identified after 6-8 days on the basis of morphological characteristics. Bacterial strains were identified including pigment, colony form, elevation, margin, texture and opacity. In addition, bacterial strains were tested with respect to gram reaction and biochemical characteristics. The total colonization frequency of the endophytes was maximum for B. spectabilis suggesting that this plant tissue harbored more endophytic bacteria than C. aurantifolia. On the other hand Cassytha filiformis stem, parasitizing B. spectabilis and C. aurantifolia supported a total of 4 bacterial species as endophytes but different to its host plants. Therefore, Sørensen’s quotient of similarity (QS) for the endophytic and epiphytic bacterial assemblages was zero. Overall, the endophyte and epiphyte assemblage of hosts and their parasite showed no overlap. Key words: Microflora; Host; Parasite; Endophytes; Epiphytes, phyllosphere DOI: 10.3126/eco.v17i0.4096 Ecoprint An International Journal of Ecology Vol. 17, 2010 Page: 1-8 Uploaded date: 28 December, 2010